PERAN AYAH SINGLE PARENT DALAM MENJALANKAN FUNGSI KELUARGA PADA MASYARAKAT MISKIN DI KELURAHAN NUSUKAN KECAMATAN BANJARSARI KOTA SURAKARTA - Tri Dyah Rastiti; Ratna Devi Sakuntalawati (Universitas Sebelas Maret (UNS), 2020)
The objective of this thesis research was to describe the role of single parent fathers in carrying out family functions in poor communities in Nusukan Village, Banjarsari Sub-District, Surakarta City. The theory used in this study was the role set theory proposed by Robert K. Merton. This study used a qualitative approach with naturalistic inquiry research method. The sampling technique used was snowball sampling and purposive sampling. The results showed that single parent fathers had carried out family functions. For the socialization function, fathers had become teachers and role models for their children, so that the children had good character. Affection function showed that the fathers became children’s playmate, so that the children became more excited and formed self-confidence and independence. In addition, the fathers had given love and affection to their children. The status determination function showed that the fathers had provided support to the children and appreciated their potential. The protection function showed that the fathers had protected and taught discipline to their children. For the economic function, the fathers had fulfilled the needs of children’s food, clothing and simple housing. In carrying out family functions, the fathers not only had social relationships with their children, such as the oldest child, neighbors, grandmother, siblings, the father’s friends, the school party, and the owner of food stalls and shops.